Thromboelastometry for Assessing Risks of Free Flap Thrombosis in Patients Undergoing Microvascular Surgery - Vanags, Indulis; Stepanovs, Jevgenijs; Ozolina, Agnese; Mukans, Maksims; Bjertnaes, Lars J.; Mamaja, Biruta (Frontiers in Medicine, 2020)
Introduction: Coagulation assessment is often missing in microvascular surgery. We aimed at evaluating the predictive value of thromboelastometry for free flap thrombosis in microvascular surgery patients. Materials and Methods: We enrolled 103 adult trauma patients scheduled for microvascular free flap surgery into a prospective observational study. Thirty-six patients with recent trauma (RT group) undergoing surgery within 30 days were compared with 67 non-recent trauma patients (non-RT group) undergoing surgery later than 30 days after traumatic event. Rotational thromboelastometry (RTE) was performed before surgery. Functional fibrinogen to platelet ratio (FPR) ≥ 42 was selected as the main hypercoagulability index. Free flap thrombosis was set as primary outcome. Thrombotic risk factors and duration of surgery related to free flap thrombosis were secondary outcomes. Statistical significance P< 0.05. Results: Six patients (16.7%) in the RT group and 10 (14.9%) in the non-RT group had free flap thrombosis (not significant). In the entire cohort, free flap thrombosis rate increased with the presence of thrombogenic comorbidities (OR 4.059, CI 1.33-12.37; p = 0.014) and prolonged surgery time (OR 1.007, CI 1 – 1.012; p = 0.05). Although hypercoagulability in the RT group (44.4%) occurred more frequently than in the non-RT group (11.9%; p < 0.001), it was not associated with higher free flap thrombosis rate. When comparing RT group patients with surgery times > 240 min, the risk of free flap thrombosis increased (OR 3.5, CI 1.16-10.6; p = 0.026) with 93.3% sensitivity and 86.7% specificity (AUC 0.85; p = 0.007). In contrast, hypercoagulability was found to increase the odds of free flap thrombosis (OR 8.83, CI 1.74-44.76; p = 0.009) in non-RT patients. Moreover, a positive correlation was found between FPR ≥ 42 and free flap thrombosis rate (r = 0.362; p = 0.003). In the non-RT group, the presence of thrombogenic comorbidities correlated with free flap thrombosis rate (OR 7, CI 1.591-30.8; p = 0.01). Conclusions: In non-RT patients with thrombogenic comorbidities, thromboelastometry supports the detection of hypercoagulability and predicts free flap thrombosis risk. In RT patients, prolonged surgery time should be considered as the main risk factor.